2003
DOI: 10.1161/01.cir.0000093280.40118.30
|View full text |Cite
|
Sign up to set email alerts
|

Control of Skin Sympathetic Nerve Activity During Intermittent Static Handgrip Exercise

Abstract: Background-Exercise activates the sympathetic nervous system as a function of the type and intensity of exercise and of the target organ studied. Although central command and activity of metabolically sensitive afferents from exercising muscle are the principal determinants of sympathetic outflow directed to skeletal muscle, the mechanisms that govern sympathetic outflow directed to skin are less clear. Methods and Results-We measured skin sympathetic nerve activity (SSNA) during intermittent static handgrip (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Blangsted et al (2004) also found no differences in trapezius muscle activity when psychosocial loads were added to computer work. Recent studies have shown a direct influence of muscular contractions on skin sympathetic activity (Leuenberger et al 2003), and that relative muscular effort influences exercise-induced skin sympathetic activity (Ray and Wilson 2004), which might partly explain our findings of increased electrodermal activity during MDT.…”
Section: Muscle Oxygenationsupporting
confidence: 50%
“…Blangsted et al (2004) also found no differences in trapezius muscle activity when psychosocial loads were added to computer work. Recent studies have shown a direct influence of muscular contractions on skin sympathetic activity (Leuenberger et al 2003), and that relative muscular effort influences exercise-induced skin sympathetic activity (Ray and Wilson 2004), which might partly explain our findings of increased electrodermal activity during MDT.…”
Section: Muscle Oxygenationsupporting
confidence: 50%
“…However, when expressed solely as total activity, this value does not identify whether changes in SSNA activation occurred via increase in amplitude and/or increase in burst frequency. Although quantification of SSNA via burst rate has been used in some studies (9,11,12,16), SSNA burst number can be very difficult to count, because integrated SSNA bursts are irregular and are not synchronized with the cardiac cycle (7), and some bursts have more than one peak (Fig. 1).…”
Section: Perspectivesmentioning
confidence: 99%
“…This exercise-induced increase in skin sympathetic nerve activity (SSNA) is controlled by the engagement of central command and activation of muscle mechanoreceptors, and it may be controlled, under very specific conditions, by activation of muscle metaboreceptors (11). Unlike muscle sympathetic nerve activity, the precise determinants of exercise-induced increases in SSNA are equivocal.…”
mentioning
confidence: 99%